Ultrafast Independent N−H and N−C Bond Deformation Investigated with Resonant Inelastic X‐Ray Scattering. Issue 22 (4th April 2017) - Eckert, Sebastian; Norell, Jesper; Miedema, Piter S.; Beye, Martin; Fondell, Mattis; Quevedo, Wilson; Kennedy, Brian; Hantschmann, Markus; Pietzsch, Annette; Van Kuiken, Benjamin E.; Ross, Matthew; Minitti, Michael P.; et al.
Abstract: The femtosecond excited‐state dynamics following resonant photoexcitation enable the selective deformation of N−H and N−C chemical bonds in 2‐thiopyridone in aqueous solution with optical or X‐ray pulses. In combination with multiconfigurational quantum‐chemical calculations, the orbital‐specific electronic structure and its ultrafast dynamics accessed with resonant inelastic X‐ray scattering at the N 1s level using synchrotron radiation and the soft X‐ray free‐electron laser LCLS provide direct evidence for this controlled photoinduced molecular deformation and its ultrashort timescale. Abstract : The photoexcitation‐induced dynamics of 2‐thiopyridone (2‐TP) were studied by time‐resolved resonant inelastic X‐ray scattering. The spectral fingerprints of N deprotonation provide insight into the initial steps of a proton transfer process in a valence excited state. X‐ray excitation of 2‐TP induces C−N bond weakening, enabling selective bond deformations by adjusting the excitation photon energy.